Diagnosis and treatment for normal pressure hydrocephalus: From biomarkers identification to outcome improvement with combination therapy - Pao-Hui Tseng; Li-Kung Wu; Yi-Cheng Wang; Tsung-Jung Ho; Shinn-Zong Lin; Sheng-Tzung Tsai (Tzu Chi Medical Journal)
Idiopathic normal pressure hydrocephalus (iNPH), albeit characterized by gait impairment, cognitive decline, and urinary incontinence, in clinical diagnosis is poorly defined and is usually coexistent with other neurodegenerative diseases. Surgical operation with shunt implantation is the primary treatment but leads to variable outcomes. Recent studies demonstrated that the pathophysiology of iNPH may include both preceding cerebrovascular events and concomitant Alzheimer's dementia or dopaminergic degenerative neuropathology in patients' brain. These factors not only help differentiate iNPH from its mimics but also associated with the extent of symptomatic improvement after surgery. In this review, we examined these mechanisms underlying the development of iNPH and the beneficial effects of shunt surgery. Furthermore, the increasing identification and importance of biomarkers from cerebrospinal fluid and neural imaging could also predict the responsiveness of treatment. Finally, these progresses suggest that combination therapy would be necessary for iNPH treatment in the future.